Subjective Sleep Quality in Women with Premenstrual Syndrome and its Correlation with Serum Magnesium Level (International Journal of Physiology, 2020)
Background: Premenstrual Syndrome (PMS) is defined as a cyclical disorder in the late luteal phase withoccurrence of non-specific somatic, psychological or behavioural changes. Sleep disturbances are morecommon in Premenstrual syndrome. Apart from hormonal causes, micronutrients like magnesium, calciumand zinc are also involved in the pathogenesis of Premenstrual syndrome.Objective: To assess the Subjective sleep quality in women with Premenstrual Syndrome and its correlationwith serum Magnesium level.Method: It is a cross- sectional study involving 175 women of age group 18-40 years. After obtaining ethicalcommittee clearance, Premenstrual Syndrome is diagnosed using Premenstrual syndrome scale (PMSS).Subjective sleep quality in them are assessed using Pittsburgh Sleep Quality Index (PSQI) and then 5 ml ofvenous blood are collected for Serum Magnesium Level estimation.Results: Among the study population of 175 women with PMS, good sleep quality was reported by 87women (49.71%) and poor sleep quality by 88 women (50.29%). The mean value of serum Magnesium levelwas 1.74 ± 0.56 mg/dl. Using Pearson’s coefficient correlation, there was a positive correlation betweensleep quality and serum magnesium level which was statistically significant.Conclusion: Magnesium replacement therapy could be beneficial in improving the poor sleep quality inPremenstrual syndrome